Vestibular schwannoma: structural characteristics, objectification of metabolic dysfunction and its clinical significance (controversial and promising issues) - O.Yu. Malysheva; V.V. Vaslovych; O.G. Chernenko; V.O. Fedirko; G.A. Shmeleva; T.A. Malysheva (Українська Інтервенційна Нейрорадіологія та Хірургія)
Objective ‒ to improve the morphological diagnosis of vestibular schwannoma (VS) based on the assessment of structural characteristics and features of stromal and perenchymal changes. Materials and methods. We analyzed the results of diagnosis and surgical treatment of 87 patients with primary VS (main group) according to code D 33.3 in accordance with International Statistical Classification of Diseases and Related Health Problems 10th Revision and the classification of central nervous system tumors (5th edition of WHO, 2021). The VS located on the left side was diagnosed in 42 (48.3 %) cases [41.08; 55.12], on the right ‒ in 45 (51.7 %) [39.15; 49.36]. Results. The morphological characteristics of vestibular schwannoma deserve special attention, as despite the high degree of tumor differentiation, their course is aggressive: they recur, cause complications, and lead to disability. Important morphological features include involutional (dystrophic-degenerative) changes in the tumor tissue, which form during the slow growth of vestibular schwannomas. In cases of solid variants of vestibular schwannoma, histological examination revealed stromal changes of varying severity, including numerous foci of hemorrhages of different ages with hemosiderosis, areas of dense sclerosis, and hyalinosis of the walls of newly formed tumor vessels. Such changes are individual metabolic alterations, partially age-related. Preliminary data on morphological characteristics (stromal-parenchymal features) in the diagnosis of vestibular schwannoma, structural signs of metabolic dysfunction, and levels of expression of histochemical markers for predicting growth rates are presented. Conclusions. Features of vestibular schwannoma based on topographic-anatomical characteristics include differences between clinical groups (Koos stages) regarding the preferential direction of spread: oral, medial, and caudal (Wilks' criterion λ = 0.105, p < 0.0001), which have specific clinical manifestations and are statistically significant. Certain immunohistochemical indicators were studied: Ki-67, progesterone receptors (RP), and the distribution of expression activity of vascular endothelial growth factor (VGFR). The low proliferative potential of vestibular schwannoma (on average—2.8% by Ki-67 proliferation index) indicates a low degree of malignancy, but with signs of chronic hypoxia. In tumor tissue with a high level of vascular endothelial growth factor, a rapid progressive course of the disease is possible. The number of cells expressing steroid hormone receptors (progesterone) partially explains their higher incidence in middle-aged women. These data require further research and comparison with clinical data.